Desenvolvimento de método baseado em espectrometria de emissão óptica com plasma induzido por micro-ondas para quantificar silício em celulose do tipo kraft - Rodrigues, Valdemir Antonio de Camargo (2023)
Cellulose is a material that is present in several products consumed by society on a daily basis, including textile, food, personal hygiene and paper products. The pulp industry moves billions of reais per year, generating thousands of direct and indirect jobs, and is therefore of great economic importance for the country. The pulp manufacturing process has been updated every year, in order to increase productivity with less environmental impact. Thus, new methods are needed to optimize the process and generate better results from your products. The objective of this work is to develop a new analysis method to quantify the silicon present in cellulose using spectroscopic techniques, aiming to optimize the dosage of the input that causes a large increase in this element, considering that this analysis is currently carried out by a laborious and slow method. The new method developed reduces the time of inorganic analysis and thus enables better control of the input with potential impact on production costs. Specifically, in this project, a method was developed to quantify the silicon present in cellulose samples using microwave induced plasma optical emission spectrometry (MIP OES), with the digestion of the samples performed by a microwave digester. The validation of the analytical method was carried out, aiming to guarantee the quality of reliable results in an analysis routine through its comparability and traceability. The study used magnesium silicate talc as a reference standard for evaluating the effectiveness of the digestion methodology for cellulose samples. The theoretical silicon oxide concentration value was 59.9% and 59.8% found in the laboratory, using the proposed method. The methodology was performed based on the parameters required by the INMETRO standard in DOC-CGRE-008, of August 2016, thus guaranteeing the quality and the accuracy of the results obtained. The results showed a gain in the response time of the silicon analysis with very close values between the developed method and the results of conventional analyses.